Upcycling silicon photovoltaic waste into thermoelectrics - Cao, Jing (2022)
Two decades after the rapid expansion of photovoltaics, the number of solar panels reaching end-of-life is increasing. While precious metals such as silver and copper are usually recycled, silicon, which makes up the bulk of a solar cells, goes to landfills. This is due to the defect- and impurity-sensitive nature in most silicon-based technologies, rendering it uneconomical to purify waste silicon. Thermoelectrics represents a rare class of material in which defects and impurities can be engineered to enhance the performance. This is because of the majority-carrier nature, making it defect- and impurity-tolerant. Here, the upcycling of silicon from photovoltaic (PV) waste into thermoelectrics is enabled. This is done by doping 1% Ge and 4% P, which results in a figure of merit (zT) of 0.45 at 873 K, the highest among silicon-based thermoelectrics. The work represents an important piece of the puzzle in realizing a circular economy for photovoltaics and electronic waste.